1993
DOI: 10.3109/09273949309086533
|View full text |Cite
|
Sign up to set email alerts
|

Nedocromil sodium 2% ophthalmic solution (TilavistTM) A new topical treatment for ocular allergic inflammation

Abstract: Nedocromil sodium, a non-toxic pyranoquinoline dicarboxylate, was developed as a novel topical treatment for allergic inflammatory lung diseases. With a broader pharmacological potential than the chromone compound sodium cromoglycate, nedocromil sodium has more potent antiinflammatory effects whilst maintaining a good safety profile due to rapid excretion, unmetabolized. Having the ability to stabilize both mucosal (MC(T)) and connective tissue (MC(TC)) mast cells and directly to inhibit activated cells such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…"I Nedocromil sodium is a recently developed topically effective drug which has similar, nontoxic, pharmacological properties to sodium cromoglycate but shows increased potency both in clinical tests and in the laboratory. 12 Nedocromil sodium is the more efficient inhibitor of activated inflammatory cells such as eosinophils" and, unlike sodium cromoglycate, which appears to stabilise only connective tissue type mast cells (MCTC), nedocromil sodium will also stabilise mucosal mast cells (MCT).14 Since the proportion of MCT type conjunctival mast cells is increased in VKC,4 nedocromil sodium should be a more effective treatment than sodium cromoglycate. A placebo controlled study carried out in Italy showed that nedocromil sodium 2% eye drops (Tilavist, Fisons plc), used four times daily over a 6 week period, significantly improved symptoms of 365 ElHennawi VKC and at the same time reduced inflammatory cells present in the tears.…”
Section: Producing Helper T Cells Promot-mentioning
confidence: 99%
“…"I Nedocromil sodium is a recently developed topically effective drug which has similar, nontoxic, pharmacological properties to sodium cromoglycate but shows increased potency both in clinical tests and in the laboratory. 12 Nedocromil sodium is the more efficient inhibitor of activated inflammatory cells such as eosinophils" and, unlike sodium cromoglycate, which appears to stabilise only connective tissue type mast cells (MCTC), nedocromil sodium will also stabilise mucosal mast cells (MCT).14 Since the proportion of MCT type conjunctival mast cells is increased in VKC,4 nedocromil sodium should be a more effective treatment than sodium cromoglycate. A placebo controlled study carried out in Italy showed that nedocromil sodium 2% eye drops (Tilavist, Fisons plc), used four times daily over a 6 week period, significantly improved symptoms of 365 ElHennawi VKC and at the same time reduced inflammatory cells present in the tears.…”
Section: Producing Helper T Cells Promot-mentioning
confidence: 99%
“…Nedocromil sodium has been shown to be more active against activated mucosal mast cells, and has a wider range of actions against other cell types than does sodium cromoglycate [7–9]. Thus it has the potential for greater efficacy than sodium cromoglycate in this condition and could prove a very important addition to the range of treatments available.…”
Section: Treatment Of Vernal Keratoconjunctivitismentioning
confidence: 99%
“…However, whilst VKC can result in permanent visual impairment, for example from formation of shield ulcers, the use of topical corticosteroids can cause equally serious problems such as the induction of sight threatening glaucoma and cataracts [3][4][5][6]. Nedocromil sodium is a more recent antiinflammatory drug which shares the pharmacological safety advantages of sodium cromoglycate but has a broader profile of cellular and neuronal activity [14,15]. Non-steroidal mast cell-stabilizing topical anti-inflammatory agents, particularly sodium cromoglycate, are therefore a mainstay of treatment for VKC and are useful in augmenting control of exacerbations and allowing a reduction or cessation of corticosteroid treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Any treatment which significantly reduces the requirement of steroids would be an advantage. Nedocromil sodium is a more recent antiinflammatory drug which shares the pharmacological safety advantages of sodium cromoglycate but has a broader profile of cellular and neuronal activity [14,15]. Having been shown to be more effective in in-vitro studies and animal models than cromoglycate, in particular against activated mucosal mast cells and eosinophils, nedocromil sodium has the potential for improved efficacy in VKC, and this has been supported by short-term studies in various forms of allergic conjunctivitis [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%